Pengaruh Variasi Konsentrasi Zeolit Alam Terhadap Karakteristik Minyak Hasil Pirolisis Campuran Plastik Polypropylene (PP) Dan Serbuk Kulit Durian - Rega Andreawan Ari Wahyudi Arto; Mokh. Hairul Bahri; Asroful Abidin (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
The increasing accumulation of polypropylene (PP) plastic waste and durian peel waste has become an environmental concern that requires effective and sustainable management strategies. One promising approach is the conversion of these wastes into liquid fuel through the pyrolysis process. This study aims to investigate the effect of natural zeolite addition on the quality of pyrolysis oil produced from a mixture of PP plastic waste and durian peel powder. The study is based on the principles of pyrolysis, PP plastic depolymerization, the role of biomass in co-pyrolysis, and the function of natural zeolite as a catalyst for hydrocarbon cracking. An experimental laboratory method was employed using a batch-type pyrolysis reactor operated at 400°C for 60 minutes. Natural zeolite concentrations of 5%, 10%, and 15% were applied, while the amount of durian peel powder was maintained at 5 grams for each sample. The parameters analyzed included pyrolysis oil yield, density, viscosity, and calorific value. The results showed that the addition of natural zeolite increased oil production, with the highest yield reaching 375 mL in sample D3. The highest density was obtained in sample D4 at 9.021 g/mL, while the highest viscosity and calorific value were achieved by sample D5 at 0.38 mm²/s and 5,277.01 cal/g, respectively. These findings indicate that natural zeolite significantly influences the characteristics of pyrolysis oil, with a 15% zeolite concentration providing the best energy quality based on the calorific value obtained